Carl Nielsen and Intentionality. Concerning the Editing of Nielsen’s Works - Hauge, Peter (Carl Nielsen Studies, 2003)
Compared with the ongoing debates in modern text criticism, problems concerning music editing – in particular with regard to nineteenth and early twentieth-century music – has only received scant attention. The present article seeks to explore the theories of editing modern texts with the editing of Nielsen’s musical works. There are three main sections: the first presents modern Anglo-American discussions on understanding the complexities of authorial intention and its function in an editing process. Though Gregg’s copy-text method (1950) is still very much in use, modern text critics, notably McGann, have often argued in favour of a different approach towards the concept of ‘authorial intention’, seeking to include the social context or setting; according to Tanselle, however, no satisfactory method has been proposed which could take these aspects into consideration. The second section deals with the understanding of the work-concept of music. This leads to the proposal of distinguishing between score, notation and performance when dealing with musical works. The distinction is made between those elements which are part of the work and those elements which rely on performance and performance practice conventions. The article concludes with three case studies of Nielsen’s works illustrating the complex problems concerning the determination of authorial intention – final as well as original – and the employment of versions. The works dealt with are Symphony no. 1 (1894), Masquerade (1906) and Andante tranquillo e Scherzo for string orchestra (1887).